Development of TTS Engine for Indian Accent using Modified HMM Algorithm - Sasanko Sekhar Gantayat (JOIV : International Journal on Informatics Visualization, 2018)
A text-to-speech (TTS) system converts normal language text into speech. An intelligent text-to-speech program allows people with visual impairments or reading disabilities, to listen to written works on a home computer. Many computer operating systems and day to day software applications like Adobe Reader have included text-to-speech systems. This paper is presented to show that how HMM can be used as a tool to convert text to speech.